Financial Support, Indispensable for Smes Growth in Mozambique - Sawayaa, Alen; Bhero, Shepherd (Archives of Business Research, 2022)
Universally it is recognized that support to Small and Medium Enterprises (SMEs) at their birth and during growth is essential to nurture them in order to avoid premature deaths. Without formidable support to SMEs, youths would remain unemployed and result in all sorts of economic ills such as increase in crime and youth immigration from rural areas to urban areas, or from Mozambique to the republic of South Africa. Support to SMEs can come in many forms; including support from financial institutions, from government agencies, large firms and non-governmental organizations (NGO)s to mention a few. What has not been confirmed especially in Mozambique is the fact that out of all types of support that can be rendered to SMEs, financial support is the most important and indispensable for SMEs survivability. The objective of the study was therefore to provide evidence that financial support supersedes all other support that can be made available to this important sector of the Mozambican economy. A sample of 485 SMEs was drawn from the population of SMEs in Greater Maputo representing Mozambique as a whole, using stratified random sampling methods. Greater Maputo, the capital of Mozambique was chosen as the nucleus of the study, because Maputo is the main centre of economic activities of the country. A face to face interview was conducted using structured, close-ended questionnaires to collect the primary data. Data was processed using multiple regression analysis, in order to isolate the one single variable, financial support, whist keeping the other support variables constant. The study found that of all supporting variables available for SMEs at start-up and during growth, financial support was critical and obligatory in Mozambique. It was recommended that financial institutions should be restructured to be more proactive to support SMEs in Mozambique, especially aiming at the most disadvantaged SMEs owner-managers.